Validating genome association studies for meat quality and carcass traits in pigs through gene networks and meta-analysis - Duarte, Darlene Ana Souza (2015)
A large number of quantitative trait loci (QTLs) for meat quality and carcass traits has been identified in several studies, but the genetic architecture remains poorly understood. Thus, a methodology that allows study genes and pathways that affect these traits would offers many advantages and increase the knowledge of physiological mechanisms. With this purpose, a methodology named Association Weight Matrix (AWM) was used to investigate the genetic basis of these traits and generate gene network based on the co-association of pair-wise SNPs across phenotypes. We performed genome association studies for 12 traits and 144 SNPs was found to be significant. A meta-analysis was performed to validate the results obtained in the genome association study in this present study. Some significant SNPs found in the genome association studies of this work are close to QTLs findings in the studies from meta-analysis. Therefore the results from meta-analysis corroborated those of the genome association studies of the present work. The significant SNPs from genome association studies were selected to build the AWM. Through this methodology, we could found 45 genes, these genes were used to build a gene network based on pairwise correlations between them. Besides, we identified 25 transcription factors (TF) strongly related (p-value<0.001) with genes in the network. The top three TF (Sox5, Nkx2- 5 and T) were choosing for construction of a network with their pathways and gene ontology. The genes from network and associated with this TF were involved in metabolism of adipose tissue and skeletal muscle. Our results suggest that genes and TF identified here are important in the control of meat quality and carcass traits. However, further efforts should be made in order to study in more detail the new gene-gene interactions here identified, as well as, the key transcription factors and pathways involved in these traits.